2020
DOI: 10.1080/0035919x.2020.1781291
|View full text |Cite
|
Sign up to set email alerts
|

Ecological restoration of ecosystems degraded by invasive alien plants in South African Fynbos: Is spontaneous succession a viable strategy?

Abstract: Ecological restoration is a global imperative to reverse widespread habitat loss and degradation, including by invasive alien plants. In South Africa's Core Cape Subregion, alien tree invasions are widespread and their control continues to be a major undertaking. As funding is limited, active restoration interventions are rarely implemented and the focus is on invader removalthe assumption being that ecosystems will self-repair. This paper reviews research findings from the past three decades to assess in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 150 publications
0
24
0
Order By: Relevance
“…Nonetheless, is spontaneous succession a viable strategy? (Holmes et al., 2020 ) pointed out that the ecosystems can accomplish self‐repair under the conditions which key biotic and/or abiotic thresholds have not yet been crossed. Specifically, the identity of the invader, the ecosystem type, and the efficacy of alien control would influence this process.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, is spontaneous succession a viable strategy? (Holmes et al., 2020 ) pointed out that the ecosystems can accomplish self‐repair under the conditions which key biotic and/or abiotic thresholds have not yet been crossed. Specifically, the identity of the invader, the ecosystem type, and the efficacy of alien control would influence this process.…”
Section: Discussionmentioning
confidence: 99%
“…in terms of seedbank dynamics, native species re-establishment and biotic and abiotic thresholds) means that holistic approaches (e.g. also considering ecological or restoration burns and active restoration) are critically important for successful ecological infrastructure interventions [ 40 , 41 ]. One ecological infrastructure intervention (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…clearing alien trees) applied without considering a more holistic approach (e.g. considering fire dynamics or the potential need for an active restoration) has often exacerbated problems [ 40 ]. For instance, it has been shown that within a single intervention (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation recovery will require fire where native cover is depleted, but a long duration of invasion may deplete native soil seed banks (Le Maitre et al 2011). In such cases active seed sowing is required to reintroduce lost vegetation components (Holmes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%